2013
DOI: 10.1016/j.stemcr.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The Luminal Progenitor Compartment of the Normal Human Mammary Gland Constitutes a Unique Site of Telomere Dysfunction

Abstract: Telomeres are essential for genomic integrity, but little is known about their regulation in the normal human mammary gland. We now demonstrate that a phenotypically defined cell population enriched in luminal progenitors (LPs) is characterized by unusually short telomeres independently of donor age. Furthermore, we find that multiple DNA damage response proteins colocalize with telomeres in >95% of LPs but in <5% of basal cells. Paradoxically, 25% of LPs are still capable of exhibiting robust clonogenic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 42 publications
(58 reference statements)
6
57
0
Order By: Relevance
“…The glutathione-independence of the LPs and their more differentiated LC progeny is associated with up-regulated expression of numerous enzymes that, in combination, appear able to counteract at least some of the potentially lethally mutagenic effects of the ROS levels that these cells produce. These observations add to a growing body of data revealing other mechanisms that predispose normal human luminal cells to DNA damage (28). Thus, the up-regulated expression of multiple antioxidant enzymes at the point of mammary progenitor cell restriction to the luminal lineage could contribute to multiple mechanisms that promote the death of LCs and allow lumen formation (5).…”
Section: Discussionmentioning
confidence: 82%
“…The glutathione-independence of the LPs and their more differentiated LC progeny is associated with up-regulated expression of numerous enzymes that, in combination, appear able to counteract at least some of the potentially lethally mutagenic effects of the ROS levels that these cells produce. These observations add to a growing body of data revealing other mechanisms that predispose normal human luminal cells to DNA damage (28). Thus, the up-regulated expression of multiple antioxidant enzymes at the point of mammary progenitor cell restriction to the luminal lineage could contribute to multiple mechanisms that promote the death of LCs and allow lumen formation (5).…”
Section: Discussionmentioning
confidence: 82%
“…The highest levels of AR mRNA in the mammary epithelium of mice and humans have been found within the HS-MEC-enriched population isolated by fluorescenceactivated cell sorting (FACS; Lim et al 2010, Kannan et al 2013; Table 1). Another mouse study reported a higher level of Ar mRNA within the FACS-sorted basal MEC population compared with the HS-MEC-enriched population (Kendrick et al 2008).…”
Section: Ar Expression In Mammary Epitheliummentioning
confidence: 99%
“…This is expected given the luminalspecific identity of NOTCH3 lineage-traced cells in vivo . One exception to the luminalpromoting nature of NOTCH receptor engagement is NOTCH4, expression of which is more restricted to basal MECs (Harrison et al 2010b, Kannan et al 2013) and implicates a role in maintenance of basal stem/progenitor MECs in this sub-population. This was demonstrated using mammospheres to measure stem cell self-renewal of primary human MECs in vitro, where secondary sphere capacity was increased tenfold when cells were cultured in the presence of a NOTCH-activating synthetic peptide (Dontu et al 2004).…”
Section: Notch Function In Mammary Epitheliummentioning
confidence: 99%
“…Human luminal cells in the progenitor-enriched fraction are also distinct from basal cells in their possession of very short telomeres, sufficient to initiate a DNA damage response (Kannan et al., 2013, Kurabayashi et al., 2008). The cells in this subset also contain, and are resistant to, higher levels of reactive oxygen species, which results in their accumulation of detectable oxidative DNA damage (Kannan et al., 2014).…”
Section: Main Textmentioning
confidence: 99%
“…The cells in this subset also contain, and are resistant to, higher levels of reactive oxygen species, which results in their accumulation of detectable oxidative DNA damage (Kannan et al., 2014). Comprehensive epigenomic and deep global transcriptome data further underscore the biologic differences exhibited by these three phenotypes of normal human mammary cells: i.e., EpCAM + luminal cells with and without surface CD49f, and EpCAM − basal cells that are also CD49f + (Kannan et al., 2013, Lim et al., 2009, Pellacani et al., 2016, Raouf et al., 2008). …”
Section: Main Textmentioning
confidence: 99%